NILAI MULTIKULTURAL SIKAP KEBERAGAMAAN DALAM TEKS PUISI - Muliadi Muliadi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2015)
The purpose of this research is expected to explain the value of multicultural diversity attitudes by utilizing poetry text as a data source. Research approach is hermeneutic with several work models which are utilized at semantic, reflective and existential understanding levels. Result and discussion about religiosityattitude indicate that (1) the devotion to God by individual or group shall not be claimed as the only acceptable way for God worship; (2) self-control is an attitude exerted by human in communicating with God; and (3) self-awareness/selfintrospection can bind all individuals despite tribe, religion and race